Relationship between polyphenol oxidase activity and nutrition, maturity and quality parameters in flat peach. (7th June 2013) - Pascual, Miquel; Villar, Josep M; Lordan, Joan; Fonseca, Francisco; Falguera, Víctor; Rufat, Josep
Abstract BACKGROUND Polyphenol oxidase (PPO) is one of the main factors that determine postharvest stability and therefore commercial possibilities of peach orchards. Since the activity of this enzyme depends on several variables of different nature, stating the relationships among them is essential to manage crop inputs so as to achieve the desired quality. RESULTS Multivariate projection techniques were used to identify these relationships throughout on‐tree maturation in flat peach samples that had received different fertilisation doses, but harvested in equal conditions of soluble solids, fruit weight, diameter, firmness and skin and flesh colour. A relatively low fertilisation dose that was enough to avoid any lack of nutrients provided the lowest crop yield, but also with the lowest PPO activity. Fruit N/Ca ratio turned out to be a better indicator of PPO activity than isolated nitrogen or calcium content. Nutrient analyses on leaves did not have strong correlations with any significant parameter. The most useful variables to predict PPO activity before harvest were fruit firmness and skin colour, both of them read at the onset of on‐tree maturation. Conclusion High fertilisation doses resulted in greater yields, but also with higher PPO activity, which is detrimental for the commercial chances of the fruit. © 2013 Society of Chemical Industry